In Vitro Models for Evaluating Anti-Aging Formulations: Biomolecular Efficacy, Quality, and Safety Assessment - Orsini, Gino; Augello, Francesca Rosaria; Ciafarone, Alessia; Cifone, Maria Grazia; Giuliani, Maurizio (Aesthetic Medicine, 2026)
Introduction: The advancement of anti-aging formulations, both topical and injectable, requires robust preclinical strategies to ensure their biological effectiveness, safety, and quality. In vitro models have become pivotal in this process, offering ethically sound and mechanistically insightful platforms that reduce reliance on animal testing.Objectives This review critically examines the spectrum of in vitro systems currently employed for the preclinical evaluation of anti-aging formulations.Methods: We analyzed the range of in vitro systems currently used, from conventional 2D cultures to sophisticated 3D skin equivalents and organ-on-chip technologies, to evaluate their contribution to preclinical testing.Results: These models contribute to understanding biomolecular pathways, formulation stability, and toxicological profiles.Conclusions: Regulatory trends and translational challenges are discussed, highlighting the integration of in vitro methods with omics and computational tools as a promising frontier in aesthetic medicine.